A Sociolinguistic Analysis of Code-Switching and Identity Construction at Al Rawabi School for Girls - Aulia Putri Al Jannah; Ari Khairurrijal Fahmi; Mahmoud Ali Al-Thar (UIN Sunan Gunung Djati Bandung, 2026)
Research on code-switching in Arabic media has largely focused on linguistic forms and educational background. In contrast, the role of high-prestige language varieties in constructing social hierarchy among adolescents in global digital media remains underexplored. This study addresses this gap by examining code-switching practices in the first season of the Netflix series Al Rawabi School for Girls. The study aims to analyze how Arabic-English code-switching functions as a socio-pragmatic resource for identity negotiation, power expression, and group differentiation among teenage girls. This research employs Qualitative Content Analysis (QCA) supported by Dell Hymes' SPEAKING framework and Tajfel and Turner's Social Identity Theory. A total of 83 instances of code-switching were identified and analyzed to examine the relationship between linguistic choices and social positioning. The findings reveal that code-switching is not merely an indicator of bilingual proficiency but primarily a symbolic strategy for constructing in-group solidarity and reinforcing out-group exclusion. English is associated with power, modernity, and social dominance, while Arabic serves as a marker of relational positioning and contextual identity negotiation. Among the observed data, patterns of linguistic behavior consistently reflect identity construction shaped by peer-group dynamics and media representation. This study contributes to sociolinguistic theory by demonstrating how linguistic globalization in digital media contexts facilitates the emergence of language-based social stratification and identity performance among Arab adolescents.